2020
DOI: 10.3389/fnhum.2020.00339
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Functional Brain Networks in Children With Psychogenic Non-epileptic Seizures

Abstract: Objectives: Psychogenic non-epileptic seizures (PNES) have been hypothesized to emerge in the context of neural networks instability. To explore this hypothesis in children, we applied a graph theory approach to examine connectivity in neural networks in the resting-state EEG in 35 children with PNES, 31 children with other functional neurological symptoms (but no PNES), and 75 healthy controls. Methods: The networks were extracted from Laplacian-transformed time series by a coherence connectivity estimation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…Moreover, they found that children with other functional neurological symptoms (but no PNES) showed scattered and less pronounced changes in network metrics. Radmanesh and colleagues 10 also observed that increases in some of the functional network metrics were correlated with increased arousal in children with PNES.…”
Section: Commentarymentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, they found that children with other functional neurological symptoms (but no PNES) showed scattered and less pronounced changes in network metrics. Radmanesh and colleagues 10 also observed that increases in some of the functional network metrics were correlated with increased arousal in children with PNES.…”
Section: Commentarymentioning
confidence: 93%
“…In their recent resting-state EEG study, Radmanesh and colleagues 10 used graph theory to examine neural network function in children with PNES, children with other functional neurological symptoms (but no PNES), and healthy controls. Graph theory is a relatively new tool that has been widely applied to characterize human brain network architecture.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the emerging picture from neuroscience research is that FND is a neuropsychiatric (mind–body) condition that involves complex interactions between brain, mind, body, and context—the lived experience of the child and the family. FND reflects the activation of brain regions that underpin salience detection, arousal, pain, and emotional states [3] , [5] , [54] , [55] . These regions, collectively referred to as the brain’s stress system or emotion-processing regions, are commonly activated in the context of stress (the psychological-arousal component of FND).…”
Section: Brain Mind and Body: Reconceptualizing Fndmentioning
confidence: 99%
“…These regions, collectively referred to as the brain’s stress system or emotion-processing regions, are commonly activated in the context of stress (the psychological-arousal component of FND). And because these emotion-processing regions are over-active and over-dominant, they over-connect with motor- and sensory-processing regions and disrupt motor and sensory function (the physical, motor-sensory component of FND) [3] , [5] , [54] , [55] . Given that FND thus involves both psychological and physical components, treatment needs to address both dimensions.…”
Section: Brain Mind and Body: Reconceptualizing Fndmentioning
confidence: 99%